Structure and Function of Tryptophan–Tyrosine Dyads in Biomimetic β Hairpins - McCaslin, Tyler G. (J Phys Chem B, 2019)
[Image: see text] Tyrosine–tryptophan (YW) dyads are ubiquitous structural motifs in enzymes and play roles in proton-coupled electron transfer (PCET) and, possibly, protection from oxidative stress. Here, we describe the function of YW dyads in de novo designed 18-mer, β hairpins. In Peptide M, a YW dyad is formed between W14 and Y5. A UV hypochromic effect and an excitonic Cotton signal are observed, in addition to singlet, excited state (W*) and fluorescence emission spectral shifts. In a second Peptide, Peptide MW, a Y5–W13 dyad is formed diagonally across the strand and distorts the backbone. On a picosecond timescale, the W* excited-state decay kinetics are similar in all peptides but are accelerated relative to amino acids in solution. In Peptide MW, the W* spectrum is consistent with increased conformational flexibility. In Peptide M and MW, the electron paramagnetic resonance spectra obtained after UV photolysis are characteristic of tyrosine and tryptophan radicals at 160 K. Notably, at pH 9, the radical photolysis yield is decreased in Peptide M and MW, compared to that in a tyrosine and tryptophan mixture. This protective effect is not observed at pH 11 and is not observed in peptides containing a tryptophan–histidine dyad or tryptophan alone. The YW dyad protective effect is attributed to an increase in the radical recombination rate. This increase in rate can be facilitated by hydrogen-bonding interactions, which lower the barrier for the PCET reaction at pH 9. These results suggest that the YW dyad structural motif promotes radical quenching under conditions of reactive oxygen stress.